Association of coronary calcium arc on stent expansion in patients with non-ST elevation myocardial infarction by intravascular ultrasound - Barman, Badal Chandra; Uddin, Mir Jamal; Karmakar, Pradip Kumar; Alam, Nur; Datta, Gokul Chandra; Saha, Mithun; Islam, Shafiqul (International Journal of Research in Medical Sciences, 2025)
Background: Coronary calcification indicates atherosclerotic plaque burden and contributes to stent under-expansion, leading to complications like restenosis and thrombosis. The impact of coronary calcium severity on stent expansion in NSTEMI patients remains unexplored in our population. This study aimed to evaluate the association between the coronary calcium arc and stent expansion in patients with non-ST elevation myocardial infarction (NSTEMI) using intravascular ultrasound (IVUS). Methods: This cross-sectional study was conducted at the National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from May 2019 to April 2020. A total of 109 NSTEMI patients undergoing IVUS-guided PCI for calcified lesions at NICVD were enrolled. Based on the calcium arc, 73 patients (0-180°) formed Group I, and 36 (181-270°) formed Group II. Stent expansion was measured. Ethical approval was obtained, and data were analyzed using SPSS version 23.0. Results: In this study, despite higher balloon pressures in Group II, acute diameter gain (1.5±0.4 mm vs 1.4±0.3 mm, p<0.03), acute CSA gain (5.8±1.2 vs 5.3±1.0, p<0.04), stent expansion by MLD (95.6±2.9% vs 89.6±3.3%, p<0.001), and MLA (92.7±5.1% vs 81.3±6.4%, p<0.001) were lower than in Group I. Stent expansion correlated negatively with calcium arc (MLD: r=-0.66, p<0.001; MLA: r=-0.69, p<0.001) but not with calcium length (MLD: r=0.14, p=0.1; MLA: r=0.09, p=0.36). Conclusion: Implantation of stents in calcified lesions results in less optimal stent expansion, especially in lesions with thick, eccentric calcific plaque layers.